The effect of contingency factors on activity-based costing implementation success in Iraqi manufacturing sector: A research framework - Albalaki, Faeq Malallah Mahmood; Abdullah, Zarifah; Kamardin, Hasnah (2017)
Purpose - This study aims to contribute to the understanding of the key contingency factors that are pertinent to ABC implementation in the context of the Iraqi manufacturing companies, by extending the discussion on the theoretical perspectives of product costing contingency research through the development of a holistic theoretical framework that explains the relationships between contingency factors and ABC implementation success.Since the inception of ABC as a costing system, many studies, with myriad of arguments have been conducted on the conceptualization, implementation and effectiveness of ABC (Stefano & Filho, 2013).However, these studies have specified the factors that can enhance successful implementation of ABC in a fragmented manner (Agbejule, 2006).Alareda (2015) has indicated that the industrial companies in Iraq are faced with numerous challenges which are related to the contextual environment. For instance, Alshabani and Alhadede (2010) have stressed that ignoring these contingency-based factors when designing cost systems, may represent an obstacle to the success of the implementation of modern cost management strategies. Notably, there is no one research that looks at how contingency factors such as perceived environmental uncertainty, market orientation, competitive strategy, organizational structure and IT, affect ABC implementation stage differently. Also, there is limited research on how changes in external environment, in technology and in organizational factors have caused Management Accounting (MA) changes in developing economies (Mat & Smith, 2014).Methodology - The study proposes a theoretical research framework which considers five contingency factors namely; Environmental Uncertainty, Market Orientation, Competitive Strategy, Organizational Structure and Information Technology (IT) as significant factors on the successful implementation of ABC in the context of the Iraqi manufacturing companies. Findings - There is a dearth of empirical findings on the impact of contingency factors such as environmental uncertainty, market orientation, competitive strategies, organizational structure and IT on the ABC implementation in the Iraqi context.The review of literature reflects that prior research concentrated on limited number of contingency factors that may influence ABC implementation success. More so, extant studies have not really considered market orientation as a significant factor contingent to ABC implementation success.